Fulvalene Derivatives Containing a Tetrabenzofluorene Unit: New Nonplanar Fulvalenes with High Electron Affinity - Yamada, Kenta; Shibamoto, Hiroshi; Tanigawa, Yusuke; Ishikawa, Hiroyuki; Nishida, Jun-ichi; Kitamura, Chitoshi; Kurata, Hiroyuki; Kawase, Takeshi (Synlett, 2016)
17H-Tetrabenzo[a,c,g,i]fluoren-17-one possessing a nonplanar, helicene-like structure was efficiently prepared by aerial oxidation of 17H-tetrabenzo[a,c,g,i]fluorene under mild basic conditions. A quinone methide and an unsymmetrical fulvalene containing a tetrabenzofluorene unit were synthesized from the ketone. Treatment of 17-bromotetrabenzo[a,c,g,i]fluorene with a base afforded a symmetric fulvalene as an air-sensitive blue solid. Electrochemical analyses revealed that these compounds have high electron affinities.
Keywords: conjugation; nonplanar π-systems; tetrabenzofluorenes; fulvalenes; electron acceptors; polycycles